The Impact of Corporate Social Responsibility Disclosure, Profitability, Leverage, Liquidity, and Sales Growth on Firm Value: Pengaruh CSR Disclosure, Profitability, Leverage, Liquidity, dan Sales Growth Terhadap Firm Value - Kellen Ivana Trini; Djeni lndrajati Widjaja; Nastasya Cindy Hidajat (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Firm value represents a key market-based indicator reflecting investor assessment of corporate performance and future prospects in capital markets. Specific Background In Indonesia, rapid growth of the capital market and sectoral expansion in industrials, consumer non-cyclical, and healthcare companies have intensified attention toward financial and non-financial disclosures associated with firm value. Knowledge Gap Prior empirical findings on the roles of corporate social responsibility disclosure, profitability, leverage, liquidity, and sales growth in shaping firm value remain inconsistent, particularly across specific IDX sectors and recent observation periods. Aims This study aims to examine the relationships between CSR disclosure, profitability, leverage, liquidity, and sales growth with firm value among companies listed on the Indonesia Stock Exchange during 2022–2024. Results Using 90 firm-year observations and multiple linear regression, the findings indicate that profitability shows a positive and significant association with firm value, while liquidity exhibits a negative and significant association; CSR disclosure, leverage, and sales growth demonstrate no significant relationships. Novelty This study provides recent sector-focused evidence highlighting the contrasting roles of profitability and liquidity within Indonesian listed firms during the post-pandemic period. Implications The results suggest that investors prioritize profit-generating capability over CSR disclosure and growth indicators, while excessive liquidity may signal inefficient resource allocation, offering insights for corporate financial management, investors, and regulators concerned with firm value formation. Highlights: Profit-generating capacity emerged as the strongest statistically supported driver of market valuation. Excessive short-term asset holdings were associated with lower market appraisal. Sustainability reporting and revenue expansion indicators were not decisive valuation signals. Keywords: Firm Value, Profitability, Liquidity, CSR Disclosure, Indonesia Stock Exchange